Atypical erythematous lesions in the course of biological therapy of generalized pustular psoriasis - Słowińska, Monika; Czuwara, Joanna; Rakowska, Adriana; Sicińska, Justyna; Warszawik, Olga; Kardynał, Agnieszka; Kurzeja, Marta; Kłujszo, Elżbieta (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Generalized pustular psoriasis is a rare inflammatory skin disease with severe, recurrent course and frequent coexistence with systemic symptoms. Biological therapy with TNF- α inhibitors or ustekinumab may be considered as an alternative option for patients who failed to respond to the standard therapy. Objective . Presentation of two cases of erythematous lesions in the course of biological therapy in patients with generalized pustular psoriasis. Case reports . Case no. 1. In a 27-year-old patient with generalized pustular psoriasis, after 3 years of infliximab therapy (3 mg/kg every 8 weeks), widespread erythema multiforme-like lesions appeared during upper respiratory tract infection. The skin lesions resolved after antibiotic treatment. The infliximab therapy was continued. Case no. 2 . In a 42-year-old patient after 1.5 years of ustekinumab (45 mg every 8 weeks) with cyclosporine A (3 mg/kg/day) therapy widespread erythematous lesions resembling subacute erythema annulare centrifugum-like psoriasis without pustulation were noticed. The lesions disappeared after increasing the dose of cyclosporine A to 3.6 mg/ kg/day. Ustekinumab therapy was continued. Conclusions . In the group of patients receiving biological treatment erythematous skin lesions of different aetiology, especially erythematous drug eruptions, can be observed. Complex diagnostic procedures are necessary in every case. The presented case reports indicate that the discontinuation of biological therapy is not necessary in all cases of widespread erythematous skin lesions.